Reviews of national policies for education - Austria (OECD, 1995)
OECD-Gutachten zur österreichischen Bildungspolitik. Im Mittelpunkt steht die Reform der Hochschulausbildung. Gliederung: PART ONE. Diversification of higher education in Austria - Summary of the Background Report (1. The Austrian education system 2. The discussion on the reform of the Austrian higher education 3. Organisation of the Fachhochschulen 4. The financing of the Fachhochschulen). - PART TWO. The Examiners Report (1. Introduction 2. Deregulation and decentralisation 3. Higher education and the economy 4. Reform in higher education - Universities 5. Reform in higher education - Vocational education and the Fachhochschulen 6. Conclusions and recommendations). (HoF/übernommen)
OECD publ. No. 47793
Keywords: Amtsdruckschrift; Graue Literatur; Education; Higher; Austria; Bildungspolitik; Hochqualifizierte Arbeitskräfte; Hochschule; Technologiepolitik; Österreich; Bildungssystem; Fachhochschule; Hochschulreform